Efektivitas Pelayanan Publik Di Kantor Pertanahan Kota Manado - Nensi Margaret Juliana Runturambi; Theodora M. Katiandagho; Grace A. J. Rumagit (Sam Ratulangi University, 2022)
This research aims to analyze the effectiveness of public services at the Manado City Land Office. The analytical method used in this research is quantitative analysis with a descriptive approach. The results of Kantah Manado City's research get a